Eksistensi dan Disiplin Tubuh Salik: Fenomenologi Tarekat Qadiriyah Wa Naqsabandiyah di Kabupaten Jember - Mulyono, Joko; Tamami, M. (Electronical Journal of Social and Political Sciences (E-SOSPOL), 2022)
The study of Sufism in the context of social relations and taking place in the Tarekat Qadiriyah wa Naqsabandiyah is the main focus of this research. The purpose of this study is to explain the existence and discipline of the body that exist in the followers of the Tarekat Qadiriyah Wa Naqsabandiyah and its contextualization in their social relations. In addition, the articulation of religion in today's context is important because the development of religion presents various options in implementing religious teachings. Qualitative research method with phenomenological approach is the approach used in this research. The individual experience of the salik is studied by looking at the social relations that exist in them. In carrying out the tarekat, the salik are taught by their murshid to discipline the body in the form of certain practices and remembrance to bring up rhythm with the aim of continuity in taking the spiritual path closer to Allah. In the existential realm, the salik can be said to be in a state of religious awareness, although this awareness is not completely stable and consistent because of the psychological dynamics in the salik, but with routine directions given by the mursyid, these dynamics can be minimized. Contextualization of the reality of Post-Secularism in the context of the Qodiriyah wa Naqsabandiyah tarekat, is found in the attitudes and behavior of the salik when they meet disagreements in religious life that exist in society.